The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.7717/peerj.9128
|View full text |Cite
|
Sign up to set email alerts
|

Higher carbon sequestration potential and stability for deep soil compared to surface soil regardless of nitrogen addition in a subtropical forest

Abstract: Background Labile carbon input could stimulate soil organic carbon (SOC) mineralization through priming effect, resulting in soil carbon (C) loss. Meanwhile, labile C could also be transformed by microorganisms in soil as the processes of new C sequestration and stabilization. Previous studies showed the magnitude of priming effect could be affected by soil depth and nitrogen (N). However, it remains unknown how the soil depth and N availability affect the amount and stability of the new sequest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 65 publications
2
5
0
Order By: Relevance
“…4 and 5 ), (ii) relatively sufficient nutrients in top and middle soils, and (iii) suitable pH and favorable soil structure and properties in top and middle soils ( Wang et al, 2014 ; Tian et al, 2016b ), which provided advantageous conditions for the decomposition of deciduous residues by microbes. Conversely, PI was higher in deep soils than in top and middle soils in our study, concurrent with the result of a prior study ( Liao et al, 2020 ). The proportion of residual organic carbon was calculated based on the input amount of organic carbon and emission amount of CO 2 in soils at different depths, which exhibited that the proportion of residual organic carbon was 88.88%, 88.05%, and 80.60% in top, middle, and deep soils, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…4 and 5 ), (ii) relatively sufficient nutrients in top and middle soils, and (iii) suitable pH and favorable soil structure and properties in top and middle soils ( Wang et al, 2014 ; Tian et al, 2016b ), which provided advantageous conditions for the decomposition of deciduous residues by microbes. Conversely, PI was higher in deep soils than in top and middle soils in our study, concurrent with the result of a prior study ( Liao et al, 2020 ). The proportion of residual organic carbon was calculated based on the input amount of organic carbon and emission amount of CO 2 in soils at different depths, which exhibited that the proportion of residual organic carbon was 88.88%, 88.05%, and 80.60% in top, middle, and deep soils, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Soil depth is frequently associated with new increases in CO 2 emissions ( Meyer et al, 2018 ; Liao et al, 2020 ). Throughout the incubation period, the CO 2 efflux rates and cumulative CO 2 emissions were higher in top and middle soils than in deep soils, which might be explained by the following factors: (i) high MBC and activities of soil catalase, alkaline phosphatase, and cellulase in top and middle soils ( Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The arid regions of Southwest China, such as the transition zone between Sichuan Basin and the eastern edge of the Qinghai-Tibet Plateau, the hotspots of land degradation, have experienced a massive landuse conversion of marginal farmlands (FL) to forest plantations under grain for green program of China (GGP) (Cheng et al, 2015;Liao et al, 2020). However, previous research on FL conversion in this region has mostly emphasized soil C accumulation; apart from total N (TN), other N cycling variables are rarely reported.…”
Section: Introductionmentioning
confidence: 99%
“…Gregory et al (2016) also reported higher C and N sequestration potential of deep soil Liao et al (2020). reported that C and N pools in the subsoil (below 0-30 cm) are assumed to be more stable than the topsoil due to differences in the composition of SOM and environmental conditions.…”
mentioning
confidence: 99%